Urgensi Motivasi Pelayanan Publik dalam Rekrutmen dan Seleksi CPNS: Alternatif dalam Peningkatan Kualitas Pelayanan Publik - Saili, Syamsir (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2009)
Public servants are selected people who have tasks and duties to perform the peopleâ€™s messages as well as possible. Â They have important roles and tasks in giving good quality of service to all people in a state. But, in Indonesia, there are some indications that most of Indonesian public servants did not give their good quality of services to people optimally. It is assumed that this condition is correlated with their bad motivation when they were recruited and selected to be public servants formerly. This article tries to elaborate this issue and gives alternatives to solve the problem in order to enhance the quality of public service ofÂ governmental institutions in the future. Kata Kunci: Pegawai Negeri Sipil (PNS), CPNS, Motivasi, Rekrutmen, Seleksi, Kualitas Pelayanan Publik.